IMPLIKASI GERAKAN PEOPLE’S ALLIANCE FOR DEMOCRACY (PAD) TERHADAP KEBIJAKAN LUAR NEGERI THAILAND TERKAIT HUBUNGAN BILATERAL THAILAND-KAMBOJA TAHUN 2008-2011 - Wiguna, I Putu Dedy; Priadarsini, Ni Wayan Rainy; Resen, Putu Titah Kawitri (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
ABSTRACT Political problem that happened in Thailand started by demonstrations to oppose Thaksin Sinawatra’s government that done by a group led by Sondhi Limthongkul in the end of 2005. Scandal of Shin Corp’s sale which as a important telecommunication enterprise in Thailand to foreigners at the end of January 2006 triggers many groups to involve in demontration with forming a social movement that named People’s Alliance for Democracy (PAD). PAD’s efforts in order to oppose Thaksin Sinawatra in Thailand such as demonstrations in many places, occupations of government buildings and airports. Political disorder in Thailand has great impact into bilateral relations between Cambodia and Thailand. It caused by a deal that signed by Thailand's Government which support Cambodia to propose Preah Vihear temple as world heritage site to UNESCO. That moment used by PAD to inspire nationalism of Thailand's people because of that temple still become an object of dispute between two nations. This research aimed to describe the implication of PAD movement toward Thailand’s foreign policy related to bilateral relations of Thailand and Cambodia in year 2008-2011. This research used qualitative method with descriptive genre. Key words: Social Movement, People Alliance for Democracy (PAD), Thaksin Sinawatra, Bilateral Relations